P‐134: Flexible Transparent Electrode Film with a Continuous Ag Nanofiber Network Embedded Structure for Flexible OLEDs. Issue 1 (May 2017) - Park, Juyoung; Hyun, Byung Gwan; Im, Hyeon-Gyun; An, Byeong Wan; Park, Jang-Ung; Bae, Byeong-Soo
Abstract : We report a flexible and high‐performance TCE/substrate platform by introducing electro‐spun Ag nanofiber (AgNF) and glass‐fabric reinforced hybrimer (GFRHybrimer) with high transparency and robustness. A single‐line network of AgNF, which already has a conductive path without junction, can provide high transparency and low sheet resistance, simultaneously. Moreover, GFRHybrimer matrix enhances the thermal stability of the AgNF TCE and mechanical durability of the composite film with smooth surface topography. To confirm the reliability and durability, we fabricated OLED on the AgNF/GFRHybrimer composite film and demonstrated the availability of the composite film for the next generation opto‐electronics.